EUROPEAN SECURITY ISSUES AS SEEN BY POLISH PARLIAMENTARIANS - Malinowski, Krzysztof; Nowosielski, Michał (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2018)
The article attempts to explore the views of the Polish parliamentarians on threats to the security of Europe and the EU and their implications for Poland and its relations with Germany in the context of the Ukrainian conflict, NATO transformations, divergent energy interests and the refugee crisis. We follow the hypothesis, that the opinions on the threats and conflicts in the neighborhood of Europe were consistent across party lines in Europe’s neighborhood and they suggest a strong consensus on the necessity to strengthen the cooperation in NATO. The article examines the responses of members of the Polish parliament (members of parliamentary committees on foreign and European affairs and security, members of the Polish-German parliamentary group) and all Polish members of the European Parliament to a dual survey carried out in 2015 and 2016. The questionnaire was completed by 22 respondents in the first and 21 respondents in the second survey. The respondents represented diverse political parties (Civic Platform, Law & Justice, Democratic Left Alliance, Polish People’s Party).

Artykuł jest poświęcony przeanalizowaniu poglądów polskich parlamentarzystów w sprawach zagrożeń dla bezpieczeństwa w Europie oraz ich implikacji dla Polski i jej stosunków z Niemcami w kontekście konfliktu na Ukrainie, przemian w NATO, rozbieżnych interesów w dziedzinie energii i kryzysu uchodźczego. Celem jest weryfikacja hipotezy, że opinie na temat zagrożeń i konfliktów w sąsiedztwie Europy były spójne w poprzek podziałów partyjnych i sugerują występowanie silnego konsensu w sprawie konieczności wzmocnienia współpracy w ramach NATO. Artykuł analizuje odpowiedzi członków polskiego parlamentu (członków komisji spraw zagranicznych i ds. Unii Europejskiej Sejmu i Senatu, członków polsko-niemieckiej grupy parlamentarnej) i wszystkich polskich członków Parlamentu Europejskiego w ramach podwójnego badania przeprowadzonego w 2015 i 2016 r. Kwestionariusz został wypełniony przez 22 respondentów w pierwszym i 21 w drugim badaniu. Respondenci reprezentowali różne partie polityczne (Platforma Obywatelska, Prawo i Sprawiedliwość, Sojusz Lewicy Demokratycznej, Polskie Stronnictwo Ludowe).
SPRAWY BEZPIECZEŃSTWA EUROPEJSKIEGO W OPINIACH POLSKICH PARLAMENTARZYSTÓW
Keywords: Europe’s security; Poland’s security; polish political elite; bezpieczeństwo Europy; bezpieczeństwo Polski; polskie elity polityczne